2022
DOI: 10.51966/jvas.2022.53.2.226-234
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy and validation of different diagnostic methods in detection of subclinical mastitis in farms of Bundelkhand

Abstract: A cross-sectional study was undertaken to validate the comparative efficacy of different diagnostic tests commonly used for the detection of subclinical mastitis. The study was designed to determine the specificity, sensitivity, and accuracy of common tests viz. California Mastitis Test (CMT), Indicator Paper Method (BTB), Somatic Cell Count (SCC), and Electrical Conductivity (EC) with bacterial culture as a standard, in parts of Bundelkhand region. Of the 411 samples, 295 were found to be positive for subclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…(7.46 per cent) Escherichia coli (4.48 per cent) and Streptococci (2.98 per cent). Singh and Kumar (2022) observed similar findings in cows with subclinical mastitis from three districts in the Bundelkhand region. The present study showed a substantial increase in the prevalence of CNS (40.31per cent) compared to those of Sebastian (2001) and Rathish (2014), who could isolate only 6.4 per cent and 23.81 per cent of CNS from all bacterial isolates from bovine mastitis cases, respectively.High prevalence of staphylococcal infections in dairy cattle udder has previously been recorded in large dairy farms (Song et al, 2020) which could be attributed to the contagious nature of staphylococcal infections, but high prevalence in isolated small holder dairy systems practising hand milking by individual milkers indicates that staphylococcal infection is endemic among the cattle population of the study area.…”
Section: Microbiologicalsupporting
confidence: 72%
“…(7.46 per cent) Escherichia coli (4.48 per cent) and Streptococci (2.98 per cent). Singh and Kumar (2022) observed similar findings in cows with subclinical mastitis from three districts in the Bundelkhand region. The present study showed a substantial increase in the prevalence of CNS (40.31per cent) compared to those of Sebastian (2001) and Rathish (2014), who could isolate only 6.4 per cent and 23.81 per cent of CNS from all bacterial isolates from bovine mastitis cases, respectively.High prevalence of staphylococcal infections in dairy cattle udder has previously been recorded in large dairy farms (Song et al, 2020) which could be attributed to the contagious nature of staphylococcal infections, but high prevalence in isolated small holder dairy systems practising hand milking by individual milkers indicates that staphylococcal infection is endemic among the cattle population of the study area.…”
Section: Microbiologicalsupporting
confidence: 72%